CALCULATION OF PURSE LINE DRAWING TIME WITH SHIP CAPACITY 30-50 GT AT NORTH ACEH - Roma Yuli Felina Hutapea; Ratu Sari Mardiah; Wewen Nassa Syaputra (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
The main problem with purse seine operations is the erratic purse line pull time. This greatly affects the total catch obtained in each trip. Therefore, this study aims to analyze the correlation value of purse line pull time and total catch, then analyze the effect between the two. The research method used is experimental fishing for 3 months. The implementation time was carried out in March-June 2020. The data analysis used was correlation analysis, ANOVA and regression. The correlation value (r) between purse line pulling time and total catch is 0.72 (strong). Based on the ANOVA value, which resulted in significantly different values, the purse line pull time significantly affected the total catch. The purse line pull time factor affects the total catch by 52% and 48% is influenced by other factors. The linear regression equation is y = 6261.2 - 2.3102x. The value of constant b has a negative value, so each additional purse line pull time will reduce the total catch. The results of this study can be used as the basis for the development of purse seine puller technology to improve the effectiveness and efficiency of purse seine operations.